Effects of Topical Carbonic Anhydrase Inhibitors on the Olfactory Sense - Gül, Fatih Cem; Güler, Mete; Kobat, Sabiha Gungor; Duzer, Sertac; Sakallıoğlu, Öner; Çelik, Fatih; Akyiğit, Abdulvahap (My University, 2021)
Objectives: The sense of smell plays an important role in daily life. Olfactory impairment can significantly affect an individual’s quality of life. Topical carbonic anhydrase inhibitors are commonly used to treat elevated intraocular pressure(IOP). One potential side effect of these drugs is a loss of the sense of smell. This study is an examination of changes in olfactory function in patients who used dorzolamide and brinzolamide to control IOP after a laser capsulotomy.Methods: A total of 60 patients with posterior capsule opacification were included in the study. Sniffin’ Sticks (Burghart Messtechnik GmbH, Wedel, Germany) were used to evaluate patient olfactory sensitivity before starting the topical treatment and after 1 week of treatment.Results: No statistically significant decrease in olfactory performance was observed in users of either brinzolamide or dorzolamide (p=0.705, p=0.405 respectively).Conclusion: No negative effect on the sense of smell was determined after 7 days of topical application of a carbonic anhydrase enzyme inhibitor to the eye in patients with no previous anosmia.
Keywords: Göz Hastalıkları